The Deteriorating Effect of Poor Parental Skill to Children and Teens Mental Health - John Michael Sasan; Ma. Theresa G. Kaligid; Mary Aianne Villegas (International Journal of Emerging Issues in Early Childhood Education, 2022)
Parenting style is a psychological construct that describes how parents raise their children in general. This article examines the several parenting techniques used by families. Parenting techniques are becoming increasingly important in modern society. This research demonstrates the various strategies that parents take when raising their children as well as the numerous issues with modern parenting. The core cause of most teenage mental health problems is found to be related to parenting style. Most parents employ a variety of parenting styles, based on their culture and societal demands. It describes parenting styles and how they affect children's development. The impact of socioeconomic class on parenting style is also examined in the study.